Food consumption in the Canary Islands: nutritional implications of food imports and local production - Dirk Godenau; Gloria Martin-Rodriguez; Jose Ignacio Gonzalez-Gomez; Jose Juan Caceres-Hernandez (BMC, 2022)
Abstract Background The composition of the average diet for the Canary Islands' population has been the subject of concern for the region's authorities and nutrition specialists. In this study, the composition of the average diet in the Canary Islands is estimated. Method The approach is based on secondary data on local production and external trade. The breakdown of the total volume of apparent food consumption into specific product categories marketed to the consumers is achieved by applying hypotheses about losses in the distribution process. The estimation of food intake is obtained by making assumptions about the rates of food wastage in the final stage of consumption. This consumption is expressed not only in terms of edible weight and the market value associated with different food groups according to their local or imported origin, but also in terms of their energy and nutrient content. Results The results obtained suggest a high-calorie diet, close to three thousand kilocalories per person per day, with an average cost of around eight euros per person per day. Imported products, with a lower average cost per unit of energy, provide most of the carbohydrates and fats. Conclusion This study provides a complementary approach to survey-based evidence and also offers the possibility of evaluating the contributions of local or imported food to the diet.